Genetics and breeding of phenolic content in tomato, eggplant and pepper fruits - Rosa-Martínez, Elena; Bovy, Arnaud; Plazas, Mariola; Tikunov, Yury; Prohens, Jaime; Pereira-Dias, Leandro (Frontiers in Plant Science, 2023)
Phenolic acids and flavonoids are large groups of secondary metabolites ubiquitous to the plant kingdom. They are currently in the spotlight due to the numerous health benefits associated to their consumption, as well as for their vital roles in plant biological processes and in plant-environment interaction. Tomato, eggplant and pepper are on the top ten of most consumed vegetables in the world, and their fruit accumulation profiles have been extensively characterised, showing substantial differences. A broad array of genetic and genomic tools has helped to identify QTLs and candidate genes associated to the fruit biosynthesis of phenolic acids and flavonoids. The aim of this review was to synthesize the available information making it easily available for researchers and breeders. The phenylpropanoid pathway is tightly regulated by structural genes, which are conserved across species, along with a complex network of regulatory elements like transcription factors, especially MYB family, and cellular transporters. Moreover, phenolic compounds accumulate in tissue-specific and developmental-dependent ways, as different paths of the metabolic pathway are activated/deactivated along with fruit development. We retrieved 104 annotated putative orthologues encoding for key enzymes of the phenylpropanoid pathway in tomato (37), eggplant (29) and pepper (38) and compiled 267 QTLs (217 for tomato, 16 for eggplant and 34 for pepper) linked to fruit phenolic acids, flavonoids and total phenolics content. Combining molecular tools and genetic variability, through both conventional and genetic engineering strategies, is a feasible approach to improve phenolics content in tomato, eggplant and pepper. Finally, although the phenylpropanoid biosynthetic pathway has been well-studied in Solanaceae, more research is needed on identification of the candidate genes behind many QTLs, as well as their interactions with other QTLs and genes.